1996
DOI: 10.1021/ja9602408
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Synthesis of Inorganic Fullerene-like MS2(M = Mo, W) from the Respective Trioxides and the Reaction Mechanism

Abstract: Recently, milligram quantities of MoS2 fullerene-like nanotubes and negative curvature polyhedra (generically called inorganic fullerene-like material, IF), were reproducibly obtained by a gas phase reaction from an oxide precursor (Feldman, Y.; Wasserman, E.; Srolovitz, D. J.; Tenne, R. Science 1995, 267, 222. Srolovitz, D. J.; Safran, S. A.; Homyonfer, M.; Tenne, R. Phys. Rev. Lett. 1995, 74, 1778). The present work focuses on the mechanism of the synthesis of IF-MS2 (M = W, Mo). The IF material is obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
347
2
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 371 publications
(369 citation statements)
references
References 31 publications
17
347
2
3
Order By: Relevance
“…The shift is however lower than reported for the I F-WS 2 nanostructures (i.e. at 649.1 and 551 nm, respectively) [14,45]. Our spectra thus indicate formation of WS 2 hydrothermally synthesized MoS 2 nanowires [46].…”
Section: Hscontrasting
confidence: 53%
See 2 more Smart Citations
“…The shift is however lower than reported for the I F-WS 2 nanostructures (i.e. at 649.1 and 551 nm, respectively) [14,45]. Our spectra thus indicate formation of WS 2 hydrothermally synthesized MoS 2 nanowires [46].…”
Section: Hscontrasting
confidence: 53%
“…The shift may be attributed to the strain relaxation in the 2H WS 2 crystal lattice due to the formation of curved nanostructures [13,14]. This observation was supported by the calculated cell parameters of the same a (0.31 nm) and somewhat longer c (1.26 nm) compared with those of the 2H WS 2 system (a = 0.31 and c = 1.236 nm; JCPDS card no.…”
Section: Hsmentioning
confidence: 58%
See 1 more Smart Citation
“…When these structures were projected onto a HRTEM image, the measured distances on the image appeared to be continuously increasing or decreasing, although the structures have evenly spaced shells. Therefore, bulk measurements of powder diffraction would lead to more accurate and unambiguous results, as performed previously for onion-like nanoparticles (40). The synthesis process is continuously being improved, and it produces bulk quantities of high yield WS 2 -NT, which enables bulk characterization.…”
Section: Resultsmentioning
confidence: 89%
“…Subsequently, the largescale synthesis of IF-MS 2 (M Mo, W) powder has been reported. [3][4][5] Furthermore, these IF metal dichalcogenides exhibit a variety of sizes and shapes and have been investigated by x-ray powder diffraction (XRD), 3 scanning tunneling microscopy (STM), 6 high resolution transmission electron microscopy (TEM), [3][4][5] optical absorption spectroscopy, 7 and Raman scattering. 8 The XRD analysis revealed that the bulk 2H structure of the unit cell is locally preserved within an IF particle.…”
Section: Introductionmentioning
confidence: 99%